The social benefits of kaizen initiatives in healthcare: an empirical study - Nicholas Rich (International Journal of Operations & Production Management, 2018)
AbstractPurpose – This paper aims to identify the most influential determinants of employees’ problem-solving capabilities and attitude towards kaizen initiatives in healthcare and clarify how determinants are related with these two social outcomes. Design/methodology/approach – Drawing on the input-process-outcome framework applied to kaizen initiatives, we distinguished determinants into input and process factors, and developed hypotheses on the direct effect of input and process factors on social outcomes, and the indirect effect of input factors on social outcomes through process factors. The hypotheses were tested through multiple regressions using data from 105 kaizen initiatives in two hospitals.Findings – Among the 14 determinants investigated, goal clarity, team autonomy, management support, goal difficulty and affective commitment to change are the most influential determinants of kaizen capabilities and/or employees’ attitude. Additionally, we found that goal clarity, goal difficulty, team autonomy and management support influence social outcomes directly and/or indirectly through affective commitment to change, internal processes and/or action orientation. Practical implications – Results guide healthcare practitioners in understanding how to set-up focused actions levering on specific determinants to positively influence social outcomes.Originality – This study provides an original contribution to the literature on kaizen initiatives in healthcare by empirically testing a comprehensive model of the relationship between kaizen initiatives determinants and social outcomes. Unlike previous studies, mostly anecdotal and focused on one or few determinants, this research adopted a holistic view by investigating the effect of a wide set of determinants on social outcomes through a systematic and quantitative approach.